Moderate increase of precipitation stimulates CO2 production by regulating soil organic carbon in a saltmarsh - Zhang, Lirong; Han, Guangxuan; Zhou, Lifeng; Li, Xinge; Wang, Xiaojie; Zhang, Xiaoshuai; Xiao, Leilei (Frontiers in Microbiology, 2024)
Saltmarsh is widely recognized as a blue carbon ecosystem with great carbon storage potential. Yet soil respiration with a major contributor of atmospheric CO 2 can offset its carbon sink function. Up to date, mechanisms ruling CO 2 emissions from saltmarsh soil remain unclear. In particular, the effect of precipitation on soil CO 2 emissions is unclear in coastal wetlands, due the the lack of outdoor data in real situations. We conducted a 7-year field manipulation experiment in a marsh in the Yellow River Delta, China. Soil respiration in five treatments (-60%, -40%, +0%, +40%, and +60% of precipitation) was measured in the field. Topsoils from the last three years (2019-2021) were analyzed for CO 2 production potential by microcosm experiments.Furthermore, quality and quantity of soil organic carbon and microbial function were tested. Results show that only the moderate precipitation rise of +40% induced a 66.2% increase of CO 2 production potential for the microcosm experiments, whereas other data showed a weak impact. Consistently, soil respiration was also found to be strongest at +40%. The CO 2 production potential is positively correlated with soil organic carbon, including carbon quantity and quality. But microbial diversity did not show any positive response to precipitation sizes. r-/K-strategy seemed to be a plausible explanation for biological factors. Overall, our finding reveal that a moderate precipitation increase, not decrease or a robust increase, in a marsh is likely to improve soil organic carbon quality and quantity, and bacterial oligotroph:copiotroph ratio, ultimately leading to an enhanced CO 2 production.